Social Media in English Language Learning (Idiomatic Sentences) A Comparative study of Instagram and Facebook Profesional - Momon Witriyaningsih; Indra Perdana; Misrita (JELT : Journal of English Education, Teaching and Literature, 2026)
This study examines the use of Instagram and Facebook Pro as ICT-based platforms for English language learning by analyzing user engagement indicators such as likes, comments, and viewers on the educational content uploaded by the researcher. The purpose of this study is to understand how both platforms function pedagogically and to evaluate how their engagement patterns align with findings from previous research on social media enhanced English learning. Using a mixed qualitative approach, the research employs a Systematic Literature Review (SLR) of publications from 2018–2025 combined with an empirical analysis of engagement data from both platforms. The findings reveal that Facebook Pro generates higher levels of visibility and interaction compared to Instagram, demonstrating its effectiveness in supporting discussion, reflection, and collaborative learning. These results are consistent with existing literature indicating that Facebook’s interactive features foster deeper pedagogical engagement, while Instagram’s visual and algorithm-driven nature tends to produce lighter and less reflective interaction. The study concludes that Facebook Pro serves as a more effective platform for disseminating ICT-integrated English learning materials. It is recommended that educators utilize Facebook for interactive learning activities and employ Instagram as a complementary tool to enhance visual learning within digital learning environments.